Does prosthesis design affect the need for secondary resurfacing in total knee arthroplasty? - Rotigliano, Niccolò (Orthop J Sports Med, 2016)
AIMS AND OBJECTIVES: The purpose of this retrospective consecutive study was to compare the rate of secondary resurfacing in consecutive series of five different TKA systems. It was our hypothesis that different brands of TKA show different rates of secondary resurfacing. MATERIALS AND METHODS: A retrospective study was performed on data from patients who underwent TKA without primary patellar resurfacing from 2004 to 2012 in an university affiliated hospital. The study cohort included 784 patients (m:f=302:482, mean age at surgery±SD 71±10) operated with TKA during this period. Five different cruciate-retaining TKA systems were used in consecutives series. These were the following: A) Triathlon, Stryker, Switzerland (n=296), B) PFC Sigma, DepuySynthes, Switzerland (n=215), C) LCS, DepuySynthes, Switzerland (n=80), D) Balansys, Mathys, Bettlach, Switzerland (n=129), E) Duracon, Stryker, Switzerland (n=64). Data was retrospectively obtained from our different hospital archives. Patients demographics, age at surgery, type of total knee arthroplasty were noted. In addition, the data were screened for a secondary resurfacing in each patient. On anterior-posterior, lateral and skyline view radiographs different measurements were performed. TKA component position was assessed on radiographs with respect to "The knee society total knee arthroplasty roentgenographic evaluation and scoring system (TKA-RESS). Pearson Chi square test was used to compare differences between groups (p<0.05). There was no significant difference between the groups in terms of age, gender, and radiological outcomes. RESULTS: Twenty-six of 784 patients (3.3%) underwent secondary resurfacing due to patellofemoral pain during follow-up. In group A four of 296 patients (1.4%), in group B fifteen of 215 patients (7%), in group C four of 80 patients (5%), in group D two of 129 patients (1.6%), in group E one of 64 patients (1.6%) underwent secondary patellar resurfacing during follow-up. There was a statistically significant difference between group B and A, D and E as well as between group C and A, D and E (p<0.001). CONCLUSION: Prosthesis design influences the need for secondary resurfacing of the patella. It was shown that the rate ranges from 1 to 7%. The highest rate for secondary resurfacing was found in the PFC Sigma TKA.